Examining cost of gain in Kansas feedlots - Babcock, A.; Jones, R.; Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study had three primary objectives: 1) to examine the effects that individual performance and ingredient price factors have on cost of gain; 2) to quantify the annual and/or seasonal trend in cost of gain in Kansas feedlots; and 3) to examine the difference in cost of gain between steers and heifers. For both steers and heifers, corn price was significant and positive, indicating that as the price of corn increases so does cost of gain. The price of hay, which is a feedstuff in the majority of feedlot diets, has a positive, but insignificant, effect on feeding cost of gain. As average daily gain increased, predicted cost of gain decreased for both steers and heifers, but the result was only significant in steers. Death loss had a positive impact on cost of gain, but may be a more important factor when feeding steers. The trend over time was positive. Feed conversion is positive and highly significantly related to cost of gain for both steers and heifers. As feed conversion (feed/gain) increases, the cost of gain increases. There seems to be a significant negative trend over time in the difference between steer and heifer cost of gain, and the difference seems to be seasonal.
Keywords: Beef; Gain; Feedlots